The outcome of neoadjuvant chemotherapy and the current trend of surgical treatment in young women with breast cancer: A multicenter real-world study (CSBrS-012) - Li, Yijun; Chen, Heyan; He, Jianjun; Fan, Zhimin; Zhang, Huimin (Frontiers in Public Health, 2023)
Background and objectives The relationship between age and the outcome of breast cancer neoadjuvant chemotherapy (NAC) remains controversial, and little is known about the choice of surgical treatment for young patients. In this multicenter real-world study, we sought to analyze the outcome of NAC as well as the current status and trend of surgical decision-making after NAC in young breast cancer patients. Methods The medical records of patients from 20 hospitals in different regions of China were collected retrospectively. The study population included females diagnosed with cT1-4N0-3M0 breast cancer who received NAC from January 2010 to December 2020. Results A total of 9,643 eligible patients were included, 1,945 (20.2%) of whom were ≤40 years old. Young patients tend to have a higher tumor stage and a higher proportion of Luminal B and triple-negative breast cancer (TNBC) tumors compared with the >40-year-old group. The breast pathological complete response (pCR) rate in the young group was 20.3%, and Luminal B tumor was more likely to obtain pCR in young patients. The implementation rate of breast-conserving surgery (BCS) and breast reconstruction surgery was higher in young patients and tended to increase over time. In different regions of China, there were great differences in the choice of surgical treatment after NAC among young patients. Conclusion Breast cancer in young women has unique clinical characteristics, but age does not affect the overall pCR rate. In China, the BCS rate after NAC is increasing over time but is still at a low level.